The euro area enlargement: A paradigmatic view - Dulkys, Arūnas (Publishing House of the Wrocław University of Economics, 2009)
This article discusses a hypothesis that the euro area enlargement policy is determined not only by a complex of macroeconomic, institutional and political boundaries [Dulkys 2008], but also is standing on a base of the disparity in a paradigmatic worldview and this disparity is of much higher-order than that while creating the euro area. The research methods of assessment analysis show that enormous cognitive significance lies in paradigmatic differences. The research results explain that paradigmatic shifts take place on a regular basis, but at the time of the world economic and social crises worldviews are changing and the need for new paradigms appears. For the benefit of the common public good (the euro), the EMU as the highest form of currency integration was achieved by refusing the national public goods (currencies) and the opportunity to apply the instruments of independent monetary policy. The article provides conclusions on that the euro and the euro area are not only the public goods of an individual country but also the public goods of the common area of the European Union (EU). (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 119-131